Effect of different heat treatments on the cyclic fatigue resistance of EdgeEndo files (Mustansiria Dental Journal, 2024)
Aim: The aim of this research is to evaluate and compare the cyclic fatigue fracture resistance of three different EdgeEndo file systems.Method:  A total of forty-five NiTi files of EdgeFile X7 (25 taper 6), EdgeX7 Utopia (25 taper 6), and EdgeOne Blaze Utopia (25 taper 8v) were used. Cyclic fatigue resistance was evaluated in a double-curved simulated artificial canal at 37℃ temperature. An endodontic motor (x Smart Plus; dentsply) was used. The motor rotated the files at 350 rpm speed until they fractured. Fracture length, time, and number of cycles to fracture were documented. Files examined under SEM to identify the topographic characteristics of the fractured file fragments. The statistical analysis of the results was done using the one-way ANOVA analysis of variance with Tukey HSD.Results: EdgeOne Blaze has demonstrated a significantly greater NCF compared to both EdgeX7 Utopia and EdgeX7 (P < 0.05). Additionally, there was a significant difference in the NCF among EdgeX7 Utopia and EdgeX7 (P < 0.05).Conclusion: Cyclic fatigue resistance significantly improved in the new NiTi files that have FireWire Blaze heat treatment.